A photovoice analysis of experiences during a short-term study abroad trip to Belize. Issue 5 (2nd September 2020) - Biber, Duke D.; Brandenburg, Gina
ABSTRACT: The purpose of this study was to use Photovoice to examine meaningful experiences and learning for Education and Health and Community Wellness students ( n = 9) on the short-term study abroad trip to Belize. The study used Photovoice and journal reflections as a way to learn about the perceptions of the participants and gain deeper understanding of their experiences while on a short-term study abroad trip. Seven main themes emerged from the photographs chosen by participants and corresponding reflections: (1) teaching; (2) gratitude; (3) poverty; (4) community; (5) education; (6) cultural pride; and (7) environment. Conclusions: The results are consistent with previous Photovoice research and quantitative research with short- and long-term study abroad trips. Overall, this study provides insight into perceptions of learning experiences from the perspective of rural, undergraduate college students studying abroad in a novel country and culture.